The Mediator Roles of Mothers in Father-Child Communications and Family Relationships - ÇELİK AHBAB, HİLAL (ANI YAYINCILIK, 2019)
Purpose: In many middle-class families in Turkey, mothers typically occupy a mediator role in father-child communications, meaning that messages between fathers and children (particularly regarding an important subject) are sent through mothers. This phenomenological study investigates Turkish father-child communication dynamics, the roles of mothers in this relationship, and the effects of mothers acting as mediators in communications between father and child. Research Methods: This study used Interpretative Phenomenological Analyses to reveal the essence of the relationship of participants with their fathers and their shared experiences regarding the reflection of the mother's role in the father-child relationship and common meanings that have been established. Employing a homogeneous sampling method, we conducted semi-structured interviews with 15 middle-class undergraduate students (nine female and six male students) aged 19-24 (x=21.33) in Istanbul, Turkey. Findings: Our analyses revealed the following three overarching themes that define the experiences of the participants: (i) an unsatisfactory father-child relationship, (ii) the mother: relational fulcrum of the father-child communications, and (iii) problematic emotional reactions to family-interactions. Implications for Research and Practice: This study represents a critical step towards understanding the experiences of youths raised in families wherein mothers occupy a mediator role in father-child communications. It revealed that the father-child relationship does not represent a satisfactory relationship and that this relationship is associated with a sense of deprivation by the children. A comparative evaluation of the experiences of the fathers, mothers, and children would enrich the interpretations and help to obtain a more complicated view of these family relationships. (c) 2019 Ani Publishing Ltd. All rights reserved
Keywords: father-child relationship; mother-child relationship; communication; family-interactions; Turkish families; AFFECTIONATE COMMUNICATION; INVOLVEMENT